2008
DOI: 10.1108/09604520810920068
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing improvement of service attributes using impact range‐performance analysis and impact‐asymmetry analysis

Abstract: PurposeThe aim of this paper is to describe and apply a new three‐step approach to prioritizing service attributes in formulating quality‐improvement strategies. In particular, the paper seels to demonstrate the value of impact range‐performance analysis (IRPA) and impact‐asymmetry analysis (IAA) in prioritizing quality attributes for improvement.Design/methodology/approachThe proposed new analytical framework is developed and presented. Data from a survey on satisfaction with airport passenger services are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(252 citation statements)
references
References 75 publications
5
215
0
2
Order By: Relevance
“…In airports, which have an important place in the aviation system, it is very important for the security services to be established and operated effectively, to operate the system efficiently and for passenger satisfaction. In international literature, the number of research on aviation security services is relatively high (Eboli & Mazzulla, 2009;Fodness & Murray, 2007;Enoma & Allen, 2007;Bezerra & Gomes, 2015;Kim et al, 2017;Jiang & Zhang, 2016;Suárez-Alemán & Jiménez, 2016;Ali et al, 2016;Gitto & Mancuso, 2017;Sakano et al, 2016;Wattanacharoensil et al, 2017;Alards-Tomalin et al, 2014;Pantouvakis & Renzi, 2016;Bogicevic et al, 2016;Mikulic & Prebežac, 2008;Prebezac et al, 2010;Gkritza et al, 2006;Perng et al, 2010;Bogicevic et al, 2013). However, the number of research on aviation security services in national literature is relatively low (Tuncer & Gavcar, 2014;Ateş et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In airports, which have an important place in the aviation system, it is very important for the security services to be established and operated effectively, to operate the system efficiently and for passenger satisfaction. In international literature, the number of research on aviation security services is relatively high (Eboli & Mazzulla, 2009;Fodness & Murray, 2007;Enoma & Allen, 2007;Bezerra & Gomes, 2015;Kim et al, 2017;Jiang & Zhang, 2016;Suárez-Alemán & Jiménez, 2016;Ali et al, 2016;Gitto & Mancuso, 2017;Sakano et al, 2016;Wattanacharoensil et al, 2017;Alards-Tomalin et al, 2014;Pantouvakis & Renzi, 2016;Bogicevic et al, 2016;Mikulic & Prebežac, 2008;Prebezac et al, 2010;Gkritza et al, 2006;Perng et al, 2010;Bogicevic et al, 2013). However, the number of research on aviation security services in national literature is relatively low (Tuncer & Gavcar, 2014;Ateş et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Telah ada penelitian-penelitian mengenai kepuasan ataupun ketidakpuasan pengguna pada industri transportasi udara (Bogicevic et al, 2013;Mikulic dan Prebezac, 2008;Sulzmaier, 2001). Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi kinerja infrastruktur transportasi yang berada di sekitar ibukota provinsi di seluruh Indonesia, dan hanya akan berfokus pada sektor transportasi udara.…”
Section: Pendahuluanunclassified
“…Numerous studies on the determinants of customer satisfaction have revealed a limitation of IPA; there is a growing evidence that the relationship between attribute-level performance and overall satisfaction with a service can be asymmetric and nonlinear; that is, the "importance" of attributes in creating overall customer satisfaction (OCS) may vary depending on the current level of attribute performance. Therefore, several studies [8][9][10] have indicated that managerial implications derived from IPA might be misleading. …”
Section: Importance-performance Analysis (Ipa)mentioning
confidence: 99%
“…Furthermore, five regions were divided on the basis of impact asymmetry (IA) indices, and the results were used as the service quality improvement baseline. According to Mikulić and Prebežac [9], the equations are as follows. In the equations, ri is the reward index for service items, pi is the penalty index for service items, and the index regression coefficient was obtained through multi-regression.…”
Section: Irpa and Iaamentioning
confidence: 99%